Information Resource to Support Voluntary Activities of Command-Professional Educational Institutions - E. Yu. Mazarakii (Библиосфера)
The article examines and analyzes the existing information resources on the support of voluntary activity (VA). It is shown that VA participants often lack reliable information about volunteerism, which is scattered across various information resources. To meet their information needs, it is necessary to create a single information resource that will help not only motivate VA participants to implement socially significant programs and projects, but also attract new participants in VA. The purpose of the article is to propose the structure and main blocks of the information portal to support VA. As a result of the research, the following main blocks of the information resource are identified: the experience of VA, preparation of public speeches, creative thinking, project development and management. The data of these information blocks allows the creation of a single information resource to meet the information needs of volunteers.